2021
DOI: 10.3390/su132313461
|View full text |Cite
|
Sign up to set email alerts
|

Digitainability and Financial Performance: Evidence from the Serbian Banking Sector

Abstract: This study aimed to explore the cross-section of digitalization and sustainability in banking and its effect on bank performance. The sample consisted of all of the banks (n = 25) operating in the Republic of Serbia from 2011 to 2020. The research results show that the banks focusing on digitalization and sustainability are profitable, even in the face of coronavirus disease 2019 (COVID-19). Furthermore, using the Pearson’s correlation, the study shows that the level of investment in digital transformation has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 24 publications
2
16
0
1
Order By: Relevance
“…Oleh karena itu, bank yang tidak memfokuskan penggunaan capitalnya untuk perputaran moneternya tidak dapat meningkatkan kinerja keuangan. Menurut Stefanovic et al, (2021), penggunaan capital perbankan banyak digunakan untuk mengevaluasi sistem digitalisasi keuangan perbankan, sehingga bank banyak menggunakan capitalnya untuk mengevaluasi risiko kegagalan sistem digitalisasi keuangan. Capital bank yang digunakan untuk digitalisasi akan menyebabkan bank menerima keuntungan secara jangka Panjang.…”
Section: Capital Berpengaruh Positif Terhadap Kinerja Keuangan Bank Umumunclassified
“…Oleh karena itu, bank yang tidak memfokuskan penggunaan capitalnya untuk perputaran moneternya tidak dapat meningkatkan kinerja keuangan. Menurut Stefanovic et al, (2021), penggunaan capital perbankan banyak digunakan untuk mengevaluasi sistem digitalisasi keuangan perbankan, sehingga bank banyak menggunakan capitalnya untuk mengevaluasi risiko kegagalan sistem digitalisasi keuangan. Capital bank yang digunakan untuk digitalisasi akan menyebabkan bank menerima keuntungan secara jangka Panjang.…”
Section: Capital Berpengaruh Positif Terhadap Kinerja Keuangan Bank Umumunclassified
“…However, according to a study of Chinese banks, it can potentially improve productivity in companies with relatively small assets. In another study by Stefanovic et al (2021), the relationship between digitalization and sustainable development in the Serbian banking sector showed that digitalization positively affects banks' return on equity and helps banks remain profitable even under the conditions of the global COVID-19 pandemic. Finally, Do et al (2022) found that digital transformation has a positive effect on the work of Vietnamese commercial banks, and the strength of the positive influence is directly proportional to the scale of the bank.…”
Section: Economic Growth Banks' Credit To Private Sector and Digitali...mentioning
confidence: 99%
“…Kane et al [15] defined DT as a process of promoting technology adaptation by individuals, businesses, society, and countries, as well as the total social change caused by digitalization. Some researchers [24][25][26]35,36] defined DT from an organizational perspective, while others [27,[37][38][39] defined DT from a social perspective.…”
Section: Literature Review 21 Definition Of Digital Transformationmentioning
confidence: 99%